2020
DOI: 10.3389/fphar.2020.554172
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Pharmacological Considerations for Chloroquine and Its Analogs in the Treatment for COVID-19

Abstract: COVID-19 has been announced pandemic by WHO and over 17,000,000 people infected (Till April 21st 2020). The disease is currently under control in China, with a curative rate of 86.8%. Chloroquine (CQ) is an old anti-malarial drug with good tolerability, which had proved to be effective in previous SARS-coronavirus, which spread and disappeared between 2002-2003. In vitro studies demonstrated the efficacy of CQ in curing COVID-19. Consequently, via analytical PBPK modeling, a further preliminary clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Decreased antimalarial efficacy of chloroquine over time, its high toxicity during long-term use, the lower antiparasitic activity of hydroxychloroquine, the side effects caused by both drugs, as well as the new discovered applications of them [5,6], are the main reasons to develop novel synthetic routes to modify their structures in less toxic analogues bearing better pharmacokinetic properties [7][8][9][10][11]. Since the promising in vitro efficacy of chloroquine and hydroxychloroquine against SARS-CoV-2 were firstly reported by the group of Prof. Wang [12,13], the investigations of an anticoronavirus potential of both compounds and other known therapeutics, their derivatives, are the focus of a number of research studies [14][15][16][17][18]. In this regard, the aim of the present study is to report an easily applicable and environmentally benign two-step Since the promising in vitro efficacy of chloroquine and hydroxychloroquine against SARS-CoV-2 were firstly reported by the group of Prof. Wang [12,13], the investigations of an anticoronavirus potential of both compounds and other known therapeutics, their derivatives, are the focus of a number of research studies [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Decreased antimalarial efficacy of chloroquine over time, its high toxicity during long-term use, the lower antiparasitic activity of hydroxychloroquine, the side effects caused by both drugs, as well as the new discovered applications of them [5,6], are the main reasons to develop novel synthetic routes to modify their structures in less toxic analogues bearing better pharmacokinetic properties [7][8][9][10][11]. Since the promising in vitro efficacy of chloroquine and hydroxychloroquine against SARS-CoV-2 were firstly reported by the group of Prof. Wang [12,13], the investigations of an anticoronavirus potential of both compounds and other known therapeutics, their derivatives, are the focus of a number of research studies [14][15][16][17][18]. In this regard, the aim of the present study is to report an easily applicable and environmentally benign two-step Since the promising in vitro efficacy of chloroquine and hydroxychloroquine against SARS-CoV-2 were firstly reported by the group of Prof. Wang [12,13], the investigations of an anticoronavirus potential of both compounds and other known therapeutics, their derivatives, are the focus of a number of research studies [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…Since the promising in vitro efficacy of chloroquine and hydroxychloroquine against SARS-CoV-2 were firstly reported by the group of Prof. Wang [12,13], the investigations of an anticoronavirus potential of both compounds and other known therapeutics, their derivatives, are the focus of a number of research studies [14][15][16][17][18]. In this regard, the aim of the present study is to report an easily applicable and environmentally benign two-step Since the promising in vitro efficacy of chloroquine and hydroxychloroquine against SARS-CoV-2 were firstly reported by the group of Prof. Wang [12,13], the investigations of an anticoronavirus potential of both compounds and other known therapeutics, their derivatives, are the focus of a number of research studies [14][15][16][17][18]. In this regard, the aim of the present study is to report an easily applicable and environmentally benign two-step synthetic approach to novel chloroquine and hydroxychloroquine analogues with combined modification of the heterocyclic pharmacophore as well as the amino substituent at 4th quinoline ring position.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[83,84] Anti-COVID-19 drugs, such as CQ and HCQ, are not recommended in patients with liver or renal diseases. [85,86] In this context, Risambaf and colleagues have reported that COVID-19-induced renal and hepatic failures might increase the possibility of CQ and HCQ-induced liver and renal toxicity during COVID-19 patients. [87] Many other drugs (oseltamivir, lopinavir/ritonavir, and ribavirin) are metabolized in the liver and excreted through urine.…”
Section: Drug-induced Renal Injury In Covid-19 Pharmacotherapymentioning
confidence: 99%
“…Using hydroxychloroquine with/without azithromycin showed significant cough remission plus reduction of body temperature and viral loads, however, small sample sizes and short follow-ups begat misleading efficacy [ 15 ]. On the other hand, a systematic review/meta-analysis study was represented by Peng et al illustrating the safety and efficacy of chloroquine and analogues in China as well as the pharmacological considerations to avoid chloroquine’s potential risk in busy clinic particularly in elder, paediatrics, and pregnant women [ 16 ]. Despite the above evidence, there is still an unmet need for more efficient and safer therapeutic agents that are capable of alleviating and stopping the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%